2015
DOI: 10.1128/aac.04809-14
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Eravacycline against Enterobacteriaceae and Acinetobacter baumannii, Including Multidrug-Resistant Isolates, from New York City

Abstract: Eravacycline demonstrated in vitro activity against a contemporary collection of more than 4,000 Gram-negative pathogens from New York City hospitals, with MIC 50 /MIC 90 values, respectively, for Escherichia coli of 0.12/0.5 g/ml, Klebsiella pneumoniae of 0.25/1 g/ml, Enterobacter aerogenes of 0.25/1 g/ml, Enterobacter cloacae 0.5/1 g/ml, and Acinetobacter baumannii of 0.5/1 g/ml. Activity was retained against multidrug-resistant isolates, including those expressing KPC and OXA carbapenemases. For A. baumanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 12 publications
3
89
0
1
Order By: Relevance
“…This is in contrast to the OXA-48 enzyme found in K. pneumoniae which is inhibited by avibactam, (MIC for ceftazidime = 128 µg/ml, MIC for CA = 0.75 µg/ml). Among Acinetobacter isolates, OXA-23 and OXA-24 were the predominant carbapenemases, a finding consistent with our earlier studies [16] [17]. While all P. aeruginosa in this study were reported as carbapenem resistant by the Vitek 2® system, the Check-MDR CT103 XL Microarray reported no carbapenem resistant genotypes likely due to lack of specific ampC primers for Pseudomonas aeruginosa.…”
Section: Discussionsupporting
confidence: 80%
“…This is in contrast to the OXA-48 enzyme found in K. pneumoniae which is inhibited by avibactam, (MIC for ceftazidime = 128 µg/ml, MIC for CA = 0.75 µg/ml). Among Acinetobacter isolates, OXA-23 and OXA-24 were the predominant carbapenemases, a finding consistent with our earlier studies [16] [17]. While all P. aeruginosa in this study were reported as carbapenem resistant by the Vitek 2® system, the Check-MDR CT103 XL Microarray reported no carbapenem resistant genotypes likely due to lack of specific ampC primers for Pseudomonas aeruginosa.…”
Section: Discussionsupporting
confidence: 80%
“…With regard to in vitro MIC studies, eravacycline has demonstrated MIC 90 values against Enterobacteriaceae that are 1-fold to 4-fold lower than those seen with tigecycline; however, tigecycline's MIC against E. coli C3-14 was 1 dilution lower than that of eravacycline, potentially resulting in the discordance in bacterial kill results (3,21). Similarly to eravacycline, tigecycline was not bactericidal in two of the three Enterobacteriaceae isolates, but both antimicrobials achieved Ն3-log killing against the MRSA isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, it has activity against most KPC producers. 89 It remains to be tested clinically against substantial numbers of patients with infections with CPE.…”
Section: Antimicrobial Agents Used For Treatment Of Cpe Infectionsmentioning
confidence: 99%